Performance of two candidate bovine tuberculins in the intradermal tuberculin test in South African cattle naturally infected with Mycobacterium bovis - Michel, Anita Luise (University of Pretoria, 2022)
Mini Dissertation (MSc (Tropical Animal Health))--University of Pretoria, 2020.